Mendorong pertumbuhan Ekomomi Melalui Pemberdayaan Sumber Daya manusia dalam Program Zakat Produktif Badan Amil Zakat Nasional (BAZNAS) di Lampung: pertumbuhan ekonomi, pemberdayaan SDM - Patminingsih, Astuti; Murcitaningrum, Suraya (P3M dan Jurusan Syariah dan Ekonomi Bisnis Islam STAIN Sultan Abdurrahman Kepulauan Riau, 2024)
This study aims to analyze the role of productive zakat programs managed by the National Zakat Agency (BAZNAS) in Lampung in encouraging the empowerment of human resources (HR) and community economic growth. The analyzed programs include Lampung Sejahtera, Lampung Cerdas, as well as various micro business capital assistance and education through scholarships. The analysis was conducted using two main theories, namely social assistance and maslahah. Social assistance focuses on the assistance provided to mustahiq (zakat recipients) in order to manage zakat funds independently and sustainably, while maslahah theory assesses the extent to which these programs support the fulfillment of the basic needs of human life, such as religion, soul, mind, offspring, and property. The results show that the productive zakat program of BAZNAS in Lampung has an impact on the economic and social empowerment of the community. Through the provision of business capital assistance in the form of ducks and goats, as well as educational scholarships, BAZNAS not only helps increase mustahiq income, but also improves the quality of human resources that can contribute to the local economy. The assistance provided ensures that zakat assistance is used effectively and provides long-term benefits. Meanwhile, the principle of maslahah is achieved by paying attention to five important aspects of life, namely religion, soul, mind, offspring, and property, all of which support the welfare of society.